Active fire fighting system in the dormitory building at UiTM Perak / Mohamad Amiruddin Mohamad Hairani and Muhammad Zahir Zulkernain - Mohamad Hairani, Mohamad Amiruddin; Zulkernain, Muhammad Zahir (2023)
Fires have burnt on Earth since terrestrial plants arose, providing a supply of fuel and oxygen, with major consequences for the Earth's system. The very major problem that is occurring in the current firefighting management is inadequate and unusable firefighting equipment in the building and low fire safety awareness among dormitory occupants due to dormitory management ineffectively executing their responsibility in fire safety management. This study aim of this research is to seek and demonstrate the level of awareness by the dormitory occupants regarding the usage of active firefighting equipment in the dormitory building. The study and findings of this research will help in giving suggestions for improving the firefighting system in the dormitory building and increasing the awareness level of the building occupants.